(3GdHjGf hGdCYdGe Hef LGhR ef GdUMGHI eGFI YGes
(3ChdgG (B:s
(3GdMeO ddg GdPi hYO ChdjGAg ai GdCNQg CfhGY GdfYe gPG cJGH CPcQ ajg GdUMGHI GdPjf YeQhG eGFI YGe s
(3BNQgG (B:s
(3MQa GdjGA gPG GdHGH Ydi CMO YGT ef GdUMGHI QVi Gddg Yfge eGFI YGe hGddg SHMGfg hJYGdi CYde s
(3eQJHg Ydi MQha GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B53 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg OGQ GdNWjH HGdbOS s
Keywords: (3GdJGQjNs